EVALUASI POSTUR KERJA DAN KELUHAN MUSKOLOSKELETAL PADA PEKERJA INSTALASI FARMASI - Kun Istighfaniar; Mulyono Mulyono (Universitas Airlangga, 2016)
Pharmaceuthical department is one of many department in RSUD Kota Madiun which serve hundreds of patients everyday. Workers on pharmacuthical department has been found having unnatural working posture on their work process, where many workers tend to complain about having low back pain problems. One of suspected problem is unnatural working posture. Unergonomic position, repetitive works, sit for long periods were few of ergonomics problem which occurred everyday. This research aimed to identify work posture and musculoskeletal complaint on pharmaceuthical department workers. This research used cross sectional approach, with population sample were all worker on pharmaceuthical department RSUD Kota Madiun and there are eight people in total. Primary data on this research collected using questionnaires, Body Mass Index measurements, interviews, and observations. Collected data from questionnaires, interview, and Body Mass Index measurements were processed, and the processed data will be analyzed using qualitatif methods of deep interview. The result showed most of worker were having high riks of having musculoskeletal problem based on RULA and REBA evaluation. Most of musculoskeletal complaints were located on their waist, hip, upper neck an lower neck. Hospital should give the workers egonomical training so that workers could avoid having unergonomical posture which lead to musculoskeletal problems. Workers should doing more often aerobic exercise.Keywords: muscoloskeletal complaint, work posture